T139. OXYTOCIN ENHANCES NEURAL EFFICIENCY IN INFERRING OTHERS' SOCIAL EMOTIONS IN PEOPLE AT CLINICAL HIGH RISK FOR PSYCHOSIS. (18th May 2020) - Schmidt, André; Davies, Cathy; Paloyelis, Yannis; Rutigliano, Grazia; Cappucciati, Marco; De Micheli, Andrea; Ramella-Cravaro, Valentina; Provenzani, Umberto; Scutt, Eleanor; Oliver, Dominic; Murguia, Silvia; Zelaya, Fernando; et al.
Abstract: Background: Negative symptoms are core contributors to social deficits in psychosis. However, currently available interventions do not significantly ameliorate negative symptoms or social outcomes in individuals at Clinical High Risk of Psychosis (CHR-P). Given its critical role in human social behaviour and cognition, the oxytocin (OT) system is a promising target for the treatment of social impairments in CHR-P subjects. Methods: In a double-blind, placebo-controlled, crossover design, 30 CHR-P males were studied using functional magnetic resonance imaging (fMRI) on two occasions, once after 40IU intranasal OT and once after placebo. A modified version of the Sally-Anne task was used to record brain activation during inferring others' beliefs (cognitive empathy) and social emotions (emotional empathy). The Reading the Mind in the Eyes Test was acquired to test whether OT effects were mediated by baseline social-emotional abilities. Results: OT did not modulate behavioural task performance but reduced activation in the bilateral inferior frontal gyrus compared with placebo during emotional empathy. Furthermore, the relationship between brain activation and task performance after OT administration was mediated by baseline social-emotional abilities; while task accuracy during emotional empathy increased with decreasing activation in the left inferior frontal gyrus in CHR-P individuals with low social-emotional abilities, there was no such relationship in CHR-P individual with high social-emotional abilities. Discussion: These findings suggest that OT enhances neural efficiency in inferring others' social emotions in those people at clinical high risk for psychosis with attenuated emotional empathy.